Study on Transport Properties of Chitosan Membrane in Different Types of Electrolytes - Ni Nyoman Rupiasih; Made Sumadiyasa; I Ketut Putra; Ni Made Rasmini (Institute for Research and Community Services (LPPM) ITB, 2018)
In this study, the electrical properties of chitosan membrane in different types of electrolytes were investigated by analyzing the current-voltage (I